Psychological preparation reduces preoperative anxiety in children. Randomized and double-blind trial - Dânia P. Meletti; José Fernando A. Meletti; Rodrigo P.S. Camargo; Leopoldo M. Silva; Norma S.P. Módolo (Elsevier, 2019)
Objective: To verify the effect of psychological preparation on the relief of preoperative anxiety in children and to correlate parents' and children's levels of anxiety. Method: After the approval of the institutional Research Ethics Committee and written consent of the children's parents or guardians, 118 children of both genders were prospectively selected, aged between 2 and 8 years, physical condition classification ASA I, who were treated in the pre-anesthetic evaluation ambulatory of the University Hospital and who underwent ambulatory surgeries at the same hospital. Two controlled groups of 59 children were randomized: control group basic preparation and psychological preparation group. On the day of surgery, all selected children were evaluated regarding their level of anxiety using the modified Yale Preoperative Anxiety Scale and their parents were evaluated regarding their level of anxiety through the Visual Analog Scale. The evaluator was blinded to which study group the child and family member belonged to. Results: Nine children and their family members were excluded per group when the results were analyzed. Children from the prepared group showed significant reductions in their level of anxiety in relation to the control group (p = 0.04). There was no correlation between the level of anxiety of children and their parents' levels (p = 0.78). Conclusion: The psychological preparation was effective in reducing the level of anxiety of children. However, there was no relation between the level of anxiety of children and their parents' level. Resumo: Objetivos: Verificar o efeito da preparação psicológica no alívio da ansiedade pré-operatória de crianças e avaliar se há correlação com a ansiedade dos pais. Método: Após a aprovação do Comitê de Ética e Pesquisa da Faculdade de Medicina e obtenção do consentimento pelos responsáveis dos pacientes, foram selecionadas prospectivamente 118 crianças, de ambos os sexos, entre dois e oito anos, classificação de estado físico ASA I, atendidas no ambulatório de avaliação pré-anestésica do Hospital Universitário e submetidas a cirurgias ambulatoriais. Foram randomizados dois grupos controlados de 59 crianças: grupo de preparação básica e grupo preparação psicológica. No dia da cirurgia, todas as crianças foram avaliadas em relação ao seu grau de ansiedade através da Escala de Ansiedade Pré-operatória de Yale Modificada e seus pais, avaliados quanto ao seu nível de ansiedade pela Escala Visual Analógica. O avaliador era cego sobre qual grupo do estudo a criança e seu familiar pertenciam. Resultados: Na análise dos resultados, foram excluídas nove crianças e familiares de cada grupo. As crianças do grupo preparado tiveram reduções significativas no grau de ansiedade em relação ao grupo controle, (p = 0,04). Não houve correlação entre os graus de ansiedade das crianças e seus pais (p = 0,78). Conclusão: A preparação psicológica foi eficaz na redução do grau de ansiedade das crianças no momento da cirurgia. Não houve, entretanto, relação entre os graus de ansiedade dos pais e seus filhos. Keywords: Child, Anxiety, Psychological preparation, Anesthesia, Surgery, Palavras-chave: Criança, Ansiedade, Preparação psicológica, Anestesia, Cirurgia